The Publishing Sub-Sector's Role in the Creative Economy: Boosting GDP and Business Growth in Sukoharjo, Indonesia: Peran Subsektor Penerbitan dalam Ekonomi Kreatif: Mendorong Pertumbuhan PDB dan Bisnis di Sukoharjo, Indonesia - Tri Nur Wahyudi; Muzakar Isa; Kusudyarsana (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study examines the strategic role of the publishing sector within the creative economy of Sukoharjo Regency, focusing on its contribution to gross domestic product (GDP) and employment generation from 2019 to 2023. Employing a descriptive qualitative methodology, the research utilized secondary data obtained from official government sources and applied thematic analysis to identify patterns and trends in the sector's economic impact. The findings reveal that the publishing sub-sector makes a positive and significant contribution to the regional GDP while serving as a meaningful source of employment opportunities for local residents. However, the analysis also identifies several critical constraints limiting the sector's growth potential, including limited access to capital financing, insufficient human resource capacity and skills development, and intense competitive pressure from global digital publishing platforms. These challenges hinder the sector's ability to maximize its economic potential and sustainability within the broader creative economy framework. The research suggests that enhancing the competitiveness and long-term viability of the publishing sector requires targeted policy interventions specifically designed to address capital accessibility issues, comprehensive human resource development programs to build industry-specific capabilities, and strengthened collaborative frameworks among key stakeholders including government agencies, educational institutions, and private sector entities. Such strategic approaches would enable the publishing sector to more effectively fulfill its potential as a driver of regional economic development and employment creation in Sukoharjo Regency.